Comparison Of Women’s Situation In The Labour Market In The Former GDR And Poland - Witkowska, Dorota (Comparative Economic Research. Central and Eastern Europe, 2016)
Twenty-five years have passed since the fall of the Berlin Wall and the beginning of transition in the former socialist countries. The aim of this research is to find out how women in East Germany and Poland, which followed completely different transformation patterns, have been affected by the introduction of market reforms. As a result of the investigation we found that the situation of women in both countries has been changed after the collapse of the communist system in Europe. However, women in former German Democratic Republic, following a significant decrease in their participation in the labour market in the early transition period, went on to become even more active than their counterparts in the Western lands. At the same time, in Poland the economic activity rate of women is lower than was observed before the transformation.